Potential Acclimatization and Adaptive Responses of Adult and Trans-Generation Coral Larvae From a Naturally Acidified Habitat - Kurihara, Haruko; Suhara, Yuri; Mimura, Izumi; Golbuu, Yimnang (Frontiers in Marine Science, 2020)
Coral reefs are one of the most susceptible ecosystems to ocean acidification (OA) caused by increasing atmospheric carbon dioxide (CO2). OA is suspected to impact the calcification rate of corals as well as multiple early life stages including larval and settlement stages. Meanwhile, there is now a strong interest in evaluating if organisms have the potential for acclimatization or adaptation to OA. Here, by taking advantage of a naturally acidified site in Nikko Bay, Palau where corals are presumably exposed to high CO2 conditions for their entire life history, we tested if adult and the next-generation larvae of the brooder coral Pocillopora acuta originating from the high-CO2 site are more tolerant to high CO2 conditions compared to the individuals from a control site. Larvae released from adults collected from the high-CO2 site within the bay and a control site outside the bay were reciprocally cultivated under experimental control or high-CO2 seawater conditions to evaluate their physiology. Additionally, reciprocal transplantation of adult P. acuta corals were conducted between the high-CO2 and control sites in the field. The larvae originating from the control site showed lower Chlorophyll-a content and lipid percentages when reared under high-CO2 compared to control seawater conditions, while larvae originating from the high-CO2 site did not. Additionally, all 10 individuals of adult P. acuta from control site died when transplanted within the bay, while all P. acuta corals within the bay survived at both control and high-CO2 site. Furthermore, P. acuta within the bay showed higher calcification and net photosynthesis rates when exposed to the condition they originated from. These results are one of the first results that indicate the possibility that the long-living corals could enable to show local adaptation to different environmental conditions including high seawater pCO2.